MONITORAMENTO MICROBIOLÓGICO DA MASTITE OVINA NA REGIÃO DE BAURU, SP - Lucheis, S.b (2020)
Mastitis is an acute or a chronic inflammation of the udder, represented for physical, chemical and bacteriological milk alterations. It is notable that ovine milk represents high economic importance, and it can be used in the production of cheeses and other derivates, contributing for the farmer’s recipe enlargement. However, the mastitis in animals can determine the reduction of milk quantity and quality in infected animals. This may determine lambs’ weight loss and increase animal’s mortality. By the other hand, considering Public Health issues, mastitis can cause milk nutrients losses and promote the microorganisms’ multiplication that may lead to diarrheas and to other zoonosis in humans. This study aimed to evaluate 159 sheep mastitis status in 20 small farms located in Bauru (SP) region. Of the 309 colected samples, in 97 (31.4%) were isolated microorganisms of the genus Staphylococcus sp., which them 27.5% being coagulase negative Staphylococcus and 3.9% coagulase positive Staphylococcus. Of 177 isolates, 97 (54.8%) were represented by the genus Staphylococcus sp., which them 57 (58.8%) from pure culture and 40 (41.2%) in association. Most agents isolated were sensitive to antibiotics used in the test. Thus, we could verify the isolation of infectious microorganisms such as coagulase positive and negative Staphylococcus and, as well in dairy cattle, preventive measures to obtain hygienic milk are extremely important in order to get a final product with quality and safe in food and microbiological point of view.